Uniformity of diet composition of Brown Skua chicks at different ages and between siblings - Graña Grilli, Maricel; Marti, Lucas J.; Montalti, Diego
The diet of chicks may change according to their growth and also vary between siblings due to their competitive relationship. Diet composition of 81 Brown Skua (Stercorarius antarcticus lonnbergi) chicks was analysed from regurgitated stomach contents in order to determine changes in diet composition related to chick age and differences between siblings. Fifty-nine of the samples belonged to chicks whose age was estimated by applying culmen measurement to a regression function. The remaining 22 samples belonged to 11 sibling pairs whose stomach contents were simultaneously sampled. The diet was constituted mostly by soft tissues of penguins. Marine resources were a minor part of the diet of chicks, appearing in the third week of their life. The qualitative composition of the stomach content of siblings was similar in most cases, but mass of regurgitates differed between siblings (1.3– 90.0% = 0.5–9 g), which suggests the potential existence of aggressive food monopolization by one sibling, an issue to be elucidated with further research. Fil: Graña Grilli, Maricel. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina. Ministerio de Relaciones Exteriores, Comercio Interno y Culto. Dirección Nacional del Antártico. Instituto Antártico Argentino; Argentina Fil: Marti, Lucas J. Universidad CAECE. Ciudad Buenos Aires; Argentina Fil: Montalti, Diego. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina. Ministerio de Relaciones Exteriores, Comercio Interno y Culto. Dirección Nacional del Antártico. Instituto Antártico Argentino; Argentina. Universidad Nacional de la Plata. Facultad de Ciencias Naturales y Museo. Departamento Científico Zoología Vertebrados; Argentina